Multisystem Langerhans Cell Histiocytosis in an infant - William Ji, MD; Joshua Ladner, MD; Aimee Rambie, MD; Kathleen Boyer, DO (Radiology Case Reports, 2021)
Langerhans cell histiocytosis (LCH) is a rare enigmatic disease that pre-dominantly affects children under 5 years of age. We report an interesting case of a 5 month old female diagnosed with multisystem LCH. Her disease process included osseous, pulmonary, gastrointestinal, cutaneous, hematopoietic and neurologic involvement. This case highlights the varying clinical symptoms, risk factors, pathogenesis, and management of multisystem LCH. This case also emphasizes the role of diagnostic imaging in this multifaceted disease.